Edge-Dependent Electronic and Magnetic Characteristics of Freestanding β 12-Borophene Nanoribbons - Vishkayi, Sahar Izadi; Tagani, Meysam Bagheri (Nano-Micro Letters, 2017)
This work presents an investigation of nanoribbons cut from β 12-borophene sheets by applying the density functional theory. In particular, the electronic and magnetic properties of borophene nanoribbons (BNR) are studied. It is found that all the ribbons considered in this work behave as metals, which is in good agreement with the recent experimental results. β 12-BNR has significant diversity due to the existence of five boron atoms in a unit cell of the sheet. The magnetic properties of the ribbons are strongly dependent on the cutting direction and edge profile. It is interesting that a ribbon with a specific width can behave as a normal or a ferromagnetic metal with magnetization at just one edge or two edges. Spin anisotropy is observed in some ribbons, and the magnetic moment is not found to be the same in both edges in an antiferromagnetic configuration. This effect stems from the edge asymmetry of the ribbons and results in the breaking of spin degeneracy in the band structure. Our findings show that β 12 BNRs are potential candidates for next-generation spintronic devices. Highlights: 1 Nanoribbons produced by cutting a β 12 borophene sheet (BNR) were studied using ab-initio calculations. 2 Charge accumulation was observed at the edge of X-BNRs, which make them good candidates for gas sensors. 3 Y-BNRs are potential candidates for spintronics due to strong spin anisotropy.